(untitled) (translation. a transdisciplinary journal, 2022)
I think of translation as a young plant that is still growing and taking shape, with short roots and some small flowers already blooming. Being young gives us a certain freedom: the journal’s future is not yet fixed; many decisions are yet to be taken; and we are not limited by traditions, conventions, or expectations. This issue therefore represents new elements not present in the earlier editions, differences I discuss at the end of this introduction.